Spotlight on Learning from Failure : Stablecoin Derisks The Blockchain Landscape with Wayne Chang - Chang, Wayne (O'Reilly Media, Incorporated, 2019)
Stablecoins-cryptocurrencies designed to avoid volatility-have been tried various times in the past with little to no success. Today, they're seeing a resurgence, as multiple firms work to develop their own stablecoins in an effort to solve the volatility crisis in cryptocurrency. Although nascent, these deployments have seen a wide amount of traction with both trading and application. But does the increased interest in stablecoins actually assuage the volatility crisis, and what does it mean for the future of blockchain-enabled businesses? In this edition of Spotlight on Learning from Failure, find out how stablecoins work, what opportunities and risks they present, and what to expect in the future with regard to the greater blockchain landscape. Wayne Chang will explain the history of stablecoins, how they solve for volatility issues in businesses and applications, and how they've been implemented over time. Wayne will also discuss the trade-offs between different stablecoins and how they fit into existing business models in order to drive value. Recorded on May 28, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Learning from Failure, you'll discover the lessons learned from failures both large and small. You'll discover how successful companies have addressed setbacks, missteps, and challenges and how you can grow from their examples.